Hydrogels Loaded with Methylene Blue: Sorption-Desorption and Antimicrobial Photoactivation Study - O. Nadtoka; P. Virych; N. Kutsevol (International Journal of Polymer Science)
Cross-linked dextran-graft-polyacrylamide hydrogels with different cross-linking density loaded with methylene blue was prepared as light-activated antimicrobial materials. Sorption/desorption properties of hydrogels were studied by estimating the change in the absorption maximum of MB solutions. The sorption/desorption rate of MB into/out of hydrogel depends on the hydrogel structure. The antibacterial properties of the light-irradiated materials were tested against Staphylococcus aureus. It was shown that irradiation of hydrogels in the presence of methylene blue was able to eliminate the bacteria strains.